Ethnobotanical study on wild edible plants used by three trans-boundary ethnic groups in Jiangcheng County, Pu'er, Southwest China - Yilin Cao; Ren Li; Shishun Zhou; Liang Song; Ruichang Quan; Huabin Hu (BMC, 2020)
Abstract Background Dai, Hani, and Yao people, in the trans-boundary region between China, Laos, and Vietnam, have gathered plentiful traditional knowledge about wild edible plants during their long history of understanding and using natural resources. The ecologically rich environment and the multi-ethnic integration provide a valuable foundation and driving force for high biodiversity and cultural diversity in this region. However, little study has uncovered this unique and attractive culture to the world. Methods We conducted ethnobotanical survey in 20 villages of Jiangcheng County from 2016 to 2020. Altogether 109 local Dai, Hani, and Yao people were interviewed, and their traditional knowledge about wild edible plants was recorded. Voucher specimens were identified by the authors and deposited in the herbarium of Xishuangbanna Tropical Botanical Garden, Chinese Academy of Sciences (HITBC). The use value was used as a quantitative index to evaluate the consumption frequency and relative importance of the wild edible plants. The Jaccard index was calculated to assess the usage similarity of different areas. The relationship of age and recognized wild edible plants by different ethnic people was performed by R. Results A total of 211 wild edible plants, belonging to 71 families and 151 genera, were recorded. These plants were consumed as wild edible vegetables, seasonal fruits, salads, spices, sour condiments, tonic soups, tea substitutes, liquor brewing, or dyeing materials. The use value (UV), current cultivation, market availability, and the quantitative traditional knowledge inheritance situation of these wild edible plants among different generations, were analyzed. Based on the data from the threatened species list of China's higher plants and the IUCN Red List, the food plant list for Asia Elephant, the Subject Database of China Plant, and the calculated UV score, the top 30 most important wild edible plants were selected for further cultivation in some local villages. Conclusion Traditional knowledge of wild edible plants, owned by Dai, Hani, and Yao people in Jiangcheng County, is rich but at risk of being lost among the young generation. Diversified cultivation of wild edible plants by the local communities could be a solution for the sustainable use of natural resources and to conserve the endangered species in this trans-boundary region.